Edge/Fog Computing Paradigm The Concept Platforms and Applications - Raj, Pethuru (Elsevier Science & Technology, 2022)
Intro -- Edge/Fog Computing Paradigm: The Concept, Platforms and Applications -- Copyright -- Contents -- Contributors -- Preface -- Chapter One: Exploring the edge AI space: Industry use cases -- 1. The proliferation of IoT devices and sensors -- 2. Activating on-device intelligence -- 3. The artificial intelligence (AI) processing at the edge -- 4. Machine learning (ML) at the edge -- 5. Deep learning at the edge -- 6. Digging into the paradigm of edge AI -- 6.1. The blend of edge AI and 5G rekindles state-of-the-art applications -- 6.2. Person re-identification (Re-ID) (https://towardsdatascience.com/why-we-need-person-re-identification-3a45d170098b) -- 7. Edge AI for next-generation retail experiences -- 8. Edge AI for smarter cities -- 9. Edge AI for telecommunication -- 10. Conclusion -- Further reading -- Chapter Two: Edge computing: Types and attributes -- 1. Introduction -- 2. Internet of Things (IoT) edge -- 2.1. Device type and mobility -- 2.2. Service capabilities -- 2.3. Security and privacy -- 2.4. Latency requirements -- 3. On-premises edge -- 3.1. Disaggregation -- 3.2. Network requirements -- 3.3. Scalability -- 3.4. Security -- 3.5. Life cycle management -- 4. Wireless Access Edge -- 4.1. Scalability -- 4.2. Distributed RAN functions -- 4.3. Service models -- 4.4. Intelligent RAN -- 5. Network edge -- 5.1. Next Generation Central Office -- 5.2. Wireline fixed access edge -- 5.3. Physical locations -- 6. Challenges in edge computing -- 7. Multi-Access Edge Computing -- References -- Chapter Three: Industry initiatives across edge computing -- 1. Linux Foundation Edge -- 1.1. Akraino -- 1.2. EdgeXFoundary -- 1.3. EVE -- 1.4. Fledge -- 1.5. Home Edge -- 1.6. Open Horizon -- 1.7. State of the Edge -- 1.8. Baetyl -- 1.9. eKupier -- 1.10. Secure Device Onboard -- 2. Linux Foundation for Networking.
Description based on publisher supplied metadata and other sources
Keywords: Electronic books